Niewydolność Serca i Płuc, TransplantologiaA minimally invasive incision for lung transplantation: antero-axillary approach - Toyoda, Yoshiya (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Increasing attention is being paid by cardiothoracic surgeons to performing cardiothoracic surgical procedures through less invasive approaches, including the use of limited skin incisions. A limited incisional approach is described that achieves full access to the entire chest cavity and the hilum, allows the use of standard operative instruments and techniques, permits rapid, easy initiation of cardiopulmonary bypass, and is easy to learn.